Impact of plaque characteristics on the degree of functional stenosis - Araújo Gonçalves, P. (2017)
Coronary CT angiography (CCTA) is mainly regarded as a gatekeeper for invasive coronary angiography, in face of its widely recognized value to noninvasively rule out significant coronary stenosis. Nevertheless, it is also increasingly recognized that this noninvasive modality can depict several atherosclerotic plaque features and quantify total coronary plaque burden. This opens a new field for cardiac CT, since these atherosclerotic features beyond stenosis severity have been correlated with the degree of functional significance, and are the focus of the present manuscript. Although recently acknowledged and documented in CCTA studies, the relation between plaque burden and functional significance has been previously described using several intracoronary imaging modalities, which are also reviewed in the manuscript, to help put in perspective the relation between anatomy and function in coronary artery disease. © Cardiovascular Diagnosis and Therapy. All rights reserved.